Association of screen exposure with psychosocial problems in primary school students - Hu, Zedan; Bi, Sitong; Wang, Wei; Liu, Chunjing; Li, Lihua (Frontiers in Pediatrics, 2023)
This study aimed to investigate the current status of screen exposure and the factors related to the screen exposure in the primary school students, and explore the relationship between screen exposure and psychosocial problems, which may provide evidence for scientific use of electronic products and psychological interventions used in these children. The parents of 811 primary school students aged 6-12 years received questionnaire survey in Beijing between January 13 to January 16, 2022. The demographic data and daily time of screen exposure were collected, and the Strengths and Difficulties Questionnaire (SDQ) about their children online was administered. In 793 students, the average daily screen exposure < 2 h and ≥2 h was noted in 75.0% and 25% of patients, respectively. The mobile phone was the main medium for screen exposure (40.9%). The family economic level, parental relationship and main supervisor were related to the time of screen exposure (χ² = 44.8,14.5 and 12.4, P <0.05). Low family economic level with the monthly income cannot meet the basic living needs, poor parental relationship and the elderly responsible for supervision increased the time of screen exposure. The abnormal emotional and behavioral symptoms, conduct problems, hyperactivity inattention, peer communication, prosocial behaviors and total difficulty score were found in 11.6%, 9.8%, 15.3%, 22.1%, 6.8% and 13.4% of children, respectively. The excessive screen exposure was related to the peer interaction and prosocial behaviors (χ²=12.18 and 7.76, P<0.05). The children with excessive screen exposure were more likely had abnormal peer interaction (χ²=12.09, P=0.001) and prosocial behaviors (χ²=7.76, P=0.005). Excessive screen exposure was a risk factor for peer interaction problems (p<0.05). In conclusion, the detection rate of excessive screen exposure is higher in primary school students, which is related to the family economic level, parental relationship and main supervisor. The excessive screen exposure is harmful to the psychosocial health of these children, which is characterized by the abnormal peer intercommunion and pro-social behaviors. More attention should be paid to the time of screen exposure in primary school students.